Global research trends in seismic landslide: A bibliometric analysis - Mengjie Yang; Shenghua Cui; Tao Jiang (Earthquake Research Advances)
Earthquake-induced landslides have always been a hot research topic in the field of geosciences. However, there have been few bibliometric analyses on this topic. To systematically understand the research status, this study is based on bibliometrics and extensively uses visualization analysis techniques. It combines quantitative and qualitative methods to conduct an in-depth analysis of 5 016 papers collected from the Web of Science (www.webofscience.com). The results revealed that: ①The number of papers on earthquake-induced landslides is steadily increasing, and is expected to continue to rise. ②Countries prone to frequent earthquakes have made significant contributions to the research on earthquake-induced landslides, and the frequent and effective cooperation among these countries has had a very positive impact on promoting landslide study. ③ Research on earthquake-induced landslides is no longer limited to the field of geology, and the future direction is to integrate knowledge and technical methods from multiple disciplines. In the research methods of earthquake-induced landslides, there is a gradual shift from ''experience, theory'' to ''data-driven''. This study can provide researchers in this field with information on the core research forces, evolving hot topics, and future development trends of earthquake-induced landslides.